Ethical and legal issues of aesthetic medical practice in Malaysia / Sirena Anne Maiks - Maiks, Sirena Anne (2019)
There are many challenges posed in this field of Aesthetic Medicine. Among which involves the ethical situation and legal impediments arising from matters concerning with the qualifications of the registered medical practitioners, the services and facilities for aesthetic medicine practice and the current in force guidelines and legislation under which the registered medical practitioners governed in Malaysia. With the rise of aesthetic medicine practice in Malaysia, the primary intention and focuses on the research is to recognise the ethical principles and related issues and also the legal position and its current challenges concerning this area of medical practice in Malaysia. It is hope for that the findings for this research will create cognisance among the health regulators, Ministry of Health, Malaysia and other stakeholders to reasonably develop a law governing the aesthetic medical practice in Malaysia and to bridge the gap in the current guideline which is in need of imperative tending. Hence, health regulators may be able to regulate the registered medical practitioners and ensure that the aesthetic medicine practice is carried out safely in this country. Most importantly, it would be able to ascertain that the outcome of this practice performed will not be detrimental to public health. Thus, pressing issues such as unauthorised practice by registered medical practitioners or unauthorised person at a licensed premise and also unlicensed premise can be curbed. It is also beneficial as the role of the registered medical practitioner in aesthetic medicine is strengthened in fulfilling the desire of the patients while protecting themselves from medical negligence. A better understanding between the patient and doctor achieved with the enhancement doctor-patient relationship produced and led to better outcomes for both parties.